Linking PHYTOCHROME-INTERACTING FACTOR to Histone Modification in Plant Shade Avoidance. Issue 2 (29th November 2017) - Peng, Maolin; Li, Zepeng; Zhou, Nana; Ma, Mengmeng; Jiang, Yupei; Dong, Aiwu; Shen, Wen-Hui; Li, Lin
Abstract : The transcription factor PIF7 recruits the H3K4me3 / H3K36me3 - reader protein MRG1 / MRG2 to promote histone acetylations in activating genes to promote stem elongation in plant shade response. Abstract: Shade avoidance syndrome (SAS) allows a plant grown in a densely populated environment to maximize opportunities to access to sunlight. Although it is well established that SAS is accompanied by gene expression changes, the underlying molecular mechanism needs to be elucidated. Here, we identify the H3K4me3/H3K36me3-binding proteins, Morf Related Gene (MRG) group proteins MRG1 and MRG2, as positive regulators of shade-induced hypocotyl elongation in Arabidopsis ( Arabidopsis thaliana ). MRG2 binds PHYTOCHROME-INTERACTING FACTOR7 (PIF7) and regulates the expression of several common downstream target genes, including YUCCA8 and IAA19 involved in the auxin biosynthesis or response pathway and PRE1 involved in brassinosteroid regulation of cell elongation. In response to shade, PIF7 and MRG2 are enriched at the promoter and gene-body regions and are necessary for increase of histone H4 and H3 acetylation to promote target gene expression. Our study uncovers a mechanism in which the shade-responsive factor PIF7 recruits MRG1/MRG2 that binds H3K4me3/H3K36me3 and brings histone-acetylases to induce histone acetylations to promote expression of shade responsive genes, providing thus a molecular mechanistic link coupling the environmental light to epigenetic modification in regulation of hypocotyl elongation in plant SAS.